ANALISIS KELAYAKAN FINANSIAL USAHA TERNAK PENGGEMUKAN SAPI POTONG PADA KOMUNITAS “NATURAL TANI” DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Gantima, Febrian M.; Muis, Abdul; Effendy, Effendy (AGROTEKBIS, 2019)
This research was aimed to analyze the financial feasibility of Beef Cattle Fattening at “Natural Tani” Community. It was conducted in Oloboju Village, Subdistrict of Sigi Biromaru, Regency of Sigi in February to March 2017. The respondents were purposively determined. Data was analyzed using financial worthiness analysis consisted of 4 indicators: Net present value (NPV), net benefit cost ratio (Net B/C), internal rate of return (IRR), and payback Period (PP). The results of this research indicated that the NPV during the period of 2014 to 2018 was IDR 76.255.242; the net B/C was 1.32; the IRR was 23,44%, and the PP is 2 years 9 months. The result of the calculation by using sensitivity analysis in Beef  production which is resulting in a increased of 15 percent with the acquisition of NPV results reduce to Rp.3.767.707, Net B/C reduced to 1.01, IRR fell to 12.60 percent PP has a payback period of 3.6 years. These values indicate that as financially shows the farming at “Natural Tani” Community well worth the effort. That is, although in those circumstances, the Natural Tani Community financially still viable. These results indicates that financially Natural Tani Community feasible to operate.